Primary Dysmenorrhea Risk based on Characteristics, Dietary Habits, and Types of Exercise - Asti Dewi Rahayu Fitrianingsih; Ayu Mutiara Santanu (Faculty of Public Health, Sriwijaya University, 2021)
The young woman's frequent complaint related to reproduction health is dysmenorrhea. The incidence of primary dysmenorrhea is affected by various factors. The purpose of the study was to examine the factors affecting primary dysmenorrhea, including characteristics, dietary habits, and types of exercise. The research was quantitative research employing correlational analytic method with a cross-sectional approach. The samples of the study were 97 female college students of The Faculty of Sports and Health Education, Universitas Pendidikan Indonesia. The sampling technique used was the Consecutive Sampling technique. There were two variables related to the primary dysmenorrhea, including breakfast habits (OR: 0,007; p:0,004) and positive family history (OR: 1,14; p:0,001). Meanwhile, BMI (OR: 3,1; p:0,317), fiber consumption habits (OR: 0,129; p:0,076), types of snack (OR: 0,14; p:0,083), types of exercise (OR: 27,4; p:0,074), and the interaction of fiber consumption and breakfast habit (OR: 0,129; p:0,076) were confounding variables. Of all variables, the breakfast habit was the most affecting variable (B:5,35). By considering the negative impacts of dysmenorrhea, they should start taking breakfast every day, especially for those who have family members with primary dysmenorrhea history.